The Effect of Chlorhexidine on Bacterial Contamination of Hall Technique Elastomeric Orthodontic Separators and Gingival Health: A Pilot Study - AlNoman, Nada (2023)
Objective: To study the effect of chlorhexidine on elastomeric orthodontic separators (EOS) bacterial-colonisation and gingival-health in Hall technique (HT) patients. Material and Methods: Prospective in-vivo pilot clinical study of EOS bacterial colonisation and primary-molar gingival health assessment in 20 patients (mean age 5.45±1.27 years) requiring bilateral HT crowns (40 teeth). One side received 1-minute 0.12% chlorhexidine-soaked-EOSs (Chx-EOSs), and the other side dry-EOSs (NoChx-EOSs). The EOSs were removed five-days later and underwent a bacterial enumeration technique. Plaque (PI) and Gingival (GI) indices were assessed pre-, five-days and three-months post-treatment. Wilcoxon-Signed-Rank/McNemar-Chi-square statistics were used (p<0.05). Results: Baseline unused/packaged EOSs’ sterility check yielded zero colony-forming-units (CFU) per millilitre, but 100% of the used EOSs became colonised by oral-microorganisms. An overall trend of lower mean CFU count in Chx-EOSs (3.415± 0.78 x105 CFU/ml) compared to NoChx-EOSs (6.157±1.48 x105 CFU/ml) was observed (p=0.009). Both NoChx-EOSs and Chx-EOSs insertion sites showed evidence of gingivitis with no difference between PI and GI indices by site over time. Conclusion:There was a lower trend of bacterial colonization in chlorhexidine treated EOSs and an occurrence of gingivitis pre/post HT-treatment regardless of EOS type. The lack of difference in the gingival health may be inconclusive due to this pilot’s low power suggesting the need for robust large scale studies.